Impact of Brand Image, Brand Awareness, and Social Media Marketing on Purchase Decisions: Mediating Roles of Purchase Interest, Service Quality, and Experiential Marketing - Ida Ayu Radinia Asri Suardana; Luh Putu Mahyuni; Ni Putu Nina Eka Lestari; Ida Bagus Raka Suardana (Universitas Muhammadiyah Yogyakarta, 2024)
This research examined how brand image, brand awareness, and social media marketing influence consumers’ purchase decisions, including factors like purchase interest, service quality, and experiential marketing as mediating variables, offering valuable knowledge for marketers to enhance their understanding of consumers’ behavior. The population was Somethinc’s Instagram followers, totaling 156 samples. This study revealed that brand image did not significantly impact purchase decisions, in contrast to brand awareness, which significantly impacted purchase decisions. Purchase interest and service quality also had no significant impact on purchase decisions. Social media marketing had no significant impact on purchase decisions, but it significantly impacted experiential marketing, emphasizing its role in improving consumers’ experiences. Conversely, experiential marketing notably impacted purchase decisions, effectively mediating the impact of social media marketing on purchase decisions. This study also unveiled that purchase interest did not mediate the impact of brand image on purchase decisions, and service quality did not mediate the impact of brand awareness on purchase decisions. The findings provide valuable insights to craft more effective strategies within the modern marketing landscape, such as marketers leveraging this understanding to design approaches that prioritize creating engaging experiences for consumers.